Incidence and burden of injury at the Tokyo 2020 Paralympic Games held during the COVID-19 pandemic: a prospective cohort study of 66 045 athlete days - Derman, Wayne; Runciman, Phoebe; Eken, Maaike; Boer, Pieter-Henk; Blauwet, Cheri; Bogdos, Manos; Idrisova, Guzel; Jordaan, Esme; Kissick, James; LeVan, Philipe; Lexell, Jan; Mohammadi, Fariba; et al. (British Journal of Sports Medicine, 2022)
ObjectiveTo describe the epidemiology of injuries at the Tokyo 2020 Paralympic Games, including injuries sustained in the new sports of badminton and taekwondo.MethodsInjury data were obtained daily via the established web-based injury and illness surveillance system (WEB-IISS; 81 countries, 3836 athletes) and local organising committee medical facilities (81 countries, 567 athletes). Univariate unadjusted incidences (injuries per 1000 athlete days with 95% CIs), injury proportion (IP, %) and injury burden (days lost per 1000 athlete days) are reported.ResultsA total of 4403 athletes (1853 women, 2550 men) from 162 countries were monitored prospectively during the 3-day pre-competition and 12-day competition periods (66 045 athlete days). 386 injuries were reported in 352 athletes (IP=8.0%) with an incidence of 5.8 per 1000 athlete days (95% CI 5.3 to 6.5). Football 5-a-side (17.2), taekwondo (16.0), judo (11.6) and badminton (9.6) had the highest incidence. There was a higher incidence of injuries in the pre-competition period than in the competition period (7.5 vs 5.4; p=0.0053). Acute (sudden onset) injuries and injuries to the shoulder (0.7) and hand/fingers (0.6) were most common. Injury burden was 10.9 (8.6–13.8), with 35% of injuries resulting in time loss from training and competition.ConclusionCompared with previous Paralympic Games, there was a reduction in injury incidence but higher injury burden at the Tokyo 2020 Paralympic Games. The new sports of taekwondo and badminton had a high injury incidence, with the highest injury burden in taekwondo, compared with other sports. These findings provide epidemiological data to inform injury prevention measures for high-risk sports.